The Effect of Mother Voice Toward Baby Weight and Duration of Deep Sleep Among Premature Infant - Anatusia Fitriana; Nyimas Heny; Resi Putri Naulia (GLOBAL HEALTH SCIENCE GROUP, 2024)
Prematurity is the primary cause of newborn mortality due to complications. Good sleep quality is essential to prevent delay development. Low sucking reflex will cause aspiration and effected to nutrition absorption. However, preterm baby experienced stress would influence birth weight and deep sleep.  One of the non-pharmacological intervention is using mother voice.  Objective. The purpose of this study was to determine to determine the effect of mother voice toward baby weight and duration of  deep sleep among premature infant Methods: This research is a quasi-experiment with a two-group pre-test and post-test design approach using control and intervention groups. The instrument used in this study is form observation, weight digital record and mobile phone. Data analysis using Independent Sample T-Test Results: There is no statistically significant difference of demographic data between the two groups' intervention and control of preterm babies (p-value > 0.005). There is an increase of baby weight and the duration of deep sleep at two groups of intervention and control. There is statistical significant difference in post-test toward weight and deep sleep duration among two group (p-value = 0.00) Conclusion Nurses can enhance their quality and ability to administer developmental care for premature babies, particularly through music therapy, which includes mother's voice intervention